Complement Inhibitor Eculizumab in Atypical Hemolytic Uremic Syndrome - Mache, Christoph J. (American Society of Nephrology, 2009)
Background and objectives: Atypical hemolytic uremic syndrome (aHUS) is associated with a congenital or acquired dysregulation of the complement alternative pathway that leads to continuous complement activation on host cells causing inflammation and damage. Eculizumab, a humanized mAb against complement protein C5, inhibits activation of the terminal complement pathway. Design, setting, participants, & measurements: We report an adolescent with relapsing unclassified aHUS. On admission, a high plasma creatinine level indicated a poor prognosis, and hemodialysis had to be started. Plasma exchanges were initially effective against the microangiopathic hemolytic activity and allowed a temporary improvement of renal function with termination of hemodialysis after 7 wk. Subsequently, plasma exchanges (three times per week) failed to prevent ongoing aHUS activity and progressive renal failure. After 12 wk, aHUS treatment was switched to eculizumab. Results: Eculizumab was effective in terminating the microangiopathic hemolytic process in two aHUS relapses; however, after normalization of complement activity, aHUS recurred and ultimately led to anuric end-stage renal failure. Conclusions: In this patient, complement inhibition by eculizumab temporarily terminated the microangiopathic hemolytic activity. Nevertheless, renal damage as a result of preceding and subsequent aHUS activity resulted in end-stage renal failure; therefore, therapeutic success may depend on early administration of eculizumab. The optimal duration of treatment may be variable and remains to be determined.